Barriers and facilitators to mental health screening efforts for families in pediatric primary care. Issue 3 (27th May 2018) - Acri, Mary; Zhang, Shirley; Chomanczuk, Aminda H.; O'Brien, Kyle H; De Zitella, Maria L. Mini; Scrofani, Paige R.; Velez, Laura; Garay, Elene; Sezer, Sara; Little, Virna; Cleek, Andrew; McKay, Mary M
ABSTRACT: The purpose of this commentary was to describe the barriers and facilitators to mental health screening efforts for children between age 5 and 18 years within three primary care clinics in poverty-impacted communities as part of an integrated care model. Three screeners, two women and one male, participated in a screening effort between September and December 2015. Screeners were interviewed about their perceptions of barriers and facilitators to screening. Organizational, family, and screener-level factors were found to influence delivery of screenings to children. Given the benefits of screening in primary care settings, identifying barriers to these initiatives and ways to address them pre-emptively could potentially alter the developmental trajectory and outcomes of children at risk for serious mental health conditions.